On q-laplace and q-sumudu transforms of a product of generalized q-bessel functions - ALBAYRAK, DURMUŞ; UÇAR, FARUK (My University, 2020)
The fundamental motivation behind this article is to take account of q-Laplace and q-Sumudu transforms of the generalized q-Bessel functions. As applications, intriguing unique instances of hypotheses are likewise examined. © CSP-Cambridge.
Keywords: Q-Bessel functions; Q-Laplace transforms; Q-Sumudu transforms